Synergetic Antimicrobial Effects of Mixtures of Ethiopian Honeys and Ginger Powder Extracts on Standard and Resistant Clinical Bacteria Isolates. (17th March 2014) - Ewnetu, Yalemwork; Lemma, Wossenseged; Birhane, Nega
Abstract : Purpose . To evaluate antimicrobial effects of mixtures of Ethiopian honeys and ginger rhizome powder extracts on Staphylococcus aureus (ATCC 25923), Escherichia coli (ATCC 25922), Staphylococcus aureus (MRSA), Escherichia coli (R), and Klebsiella pneumoniae (R). Methods . Agar diffusion and broth assays were performed to determine susceptibility of these standard and resistant clinical bacteria isolates using honey-ginger powder extract mixtures. Results . Honey-ginger powder extract mixtures produced the highest mean inhibition ( 25.62   m m ± 2.55 ) compared to the use of honeys ( 21.63   m m ± 3.30 ) or ginger extracts ( 19.23   m m ± 3.42 ) individually. The ranges of inhibitions produced by honey-ginger extract mixtures on susceptible test organisms (26–30 mm) and resistant strains (range: 19–27 mm) were higher compared to 7–22 mm and 0–14 mm by standard antibiotic discs. Minimum inhibitory concentrations (MIC) of mixture of honeys-ginger extracts were 6.25% (0.625 v/mL) on the susceptible bacteria compared to 75% for resistant clinical isolates. Minimum bactericidal concentration (MBC) of honey-ginger extracts was 12.5% (0.125 g/mL) for all the test organisms. Conclusion . The result of this study showed that honey-ginger powder extract mixtures have the potential to serve as cheap source of antibacterial agents especially for the drug resistant bacteria strains.